A comprehensive study on energy trading and finance using blockchain technology - Akshat Miglani; Khush Patel; Margesh Modi; Yana Gadhvi; Manan Shah (Unconventional Resources)
As a theoretical foundation and overview, the paper explains how blockchain technology influences energy trade and finance through decentralized, safe, and transparent peer-to-peer transactions. It examines the current energy crisis that arises with a steep, rising curve of rather unorthodox consumption of energy and calls for cleaner, more reliable sources of energy. It also discusses how blockchain-based platforms could help eliminate persistent challenges in centralized energy systems. By combining the previous literature on distributed ledgers, smart contracts, and decentralized market mechanisms, we find that blockchain provides faster settlements, lower overheads, and enhanced resilience against single points of failure. This study will review how blockchain-enabled energy finance solutions speed transactions, build trust, and allow for innovative funding approaches, such as green bonds and energy banking. All in all, the findings support blockchain as a viable way of achieving a more flexible, customer-oriented, and environmentally sustainable energy sector while showcasing the technological, regulatory, and operational gaps that research and responsible policy actions must address.